Flexible digital Scrambler/De-Scrambler system - Al-Absi, Munir A (2006)
The structural design of a flexible Scramble/De-Scrambler that uses aprogrammable length shift register and modulo-2 adder is presented. The key feature of the proposed design is its flexibility in varying the length of the delay elements pseudo-randomly and hence the encryption code. In addition, the encryption code can be re-programmed by the manufacturer through the EPROM involved in the design and by the user through the loadable pseudo-random sequence generator.